ENHANCED PRIVACY PROTECTION AGAINST LOCATION-DEPENDENT ATTACKS IN LOCATION BASED SERVICES USING SPATIAL CLOAKING: Privacy Preservation in LBS (Journal of Information and Communication Technology, 2019)
Use of Internet enabled mobile devices has facilitated the rapid Use of Internet enabled mobile devices has facilitated the rapid development of location-based services (LBS). LBS allow users to access useful information such as the nearest ATM, temple, and so on. Although users enjoy the convenience of LBS, they are being exposed to the risk of location disclosures which could lead to potential abuse of location data. Hence, location privacy protection has recently received considerable attention in LBS. There are numerous techniques presented by various researchers to protect the location-context of users. Location cloaking is an often used technique to protect location-contexts. Most of the existing location cloaking algorithms are only concerned with snapshot user locations and cannot effectively prevent users from location-dependent attacks when user location-contexts are continuously updated. This paper presents a solution to protect users from location-dependent attacks by improving the existing clique based cloaking algorithm. The main idea is to maintain maximum sized cliques required for location cloaking in an undirected graph. Thus, a qualified clique can be quickly identified and used to generate a cloaked region when a new request arrives. In addition, dummy queries are generated to protect users from unusual situations. Through maximum sized cliques and dummy query generation, more user queries get cloaked within a reasonable amount of time, thereby providing cloaked within a reasonable amount of time, thereby providing better privacy protection when using LBS applications. The experimental results showed that the proposed cloaking algorithm out performed existing algorithms such as IClique, OptClique and MMBClique in terms of its cloaking success rate and processing time.